Analisis Perencanaan Kualitas terhadap Kualitas Pelayanan Logistik di Perusahaan 3PL - Deevana Putri Nabilah; Resista Vikaliana (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aimed to analyze the effect of quality planning on service quality at PT. Puninar Anji Nyk Logistics Indonesia and also to find out how much effect that the quality planning has on service quality at PT. Puninar Anji Nyk Logistics Indonesia. This study used quantitative method with the population of the customers at PT. Puninar Anji Nyk Logistics Indonesia. The sample in this study was 60 customers by using the Random Sampling method, then the data was processed by SPSS statistical analysis. The independent variable in this study was planning, and the dependent variable in this study was service quality. The results showed that Quality Planning had an effect on the Logistics Service Quality at PT. Puninar Anji Nyk Logistics Indonesia. It was evidenced by the assessment using a simple linear regression test which showed a constant value of 8.541. It means that if the variable X (Planning) was equal to zero, then the variable Y (Service Quality) was -8.541 and it was also known that the planning regression coefficient (X) was 1.546 which was positive. These results showed that every time there was an increase or decrease in Planning (X) by one unit, it was followed by an increase or decrease in customer satisfaction (Y) by 1.546 units. With the results of the t-test performed at t-value > t-table or (10.535 > 1.9) and the results of the correlation coefficient (R) of 0.810 with a scale of > 0.75-0.99 then obtained a value (R Square) of 65.7%, and the results of the Coefficient of Determination with a total R2 of 0.657 or 65.7%. So it can be concluded that H0 was rejected and H1 was accepted, which means the planning variable (X) had a significant effect on the service quality variable (Y).